Sea reclamation in XLIV urban area, Central Malacca district, Malacca : from the perspective of Heritage Impact Assessment study - Asyaari Muhamad; Amir Husaini Saiffuddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
On the coast of Central Malacca, a 75-acres sea reclamation project site has merged with the National Heritage Gazette area. From July to October 2020, a Heritage Impact Assessment (HIA) study was conducted at the reclamation project site to decide whether the reclamation project shall continue or need to be relocated to another location. Based on several previous survey studies and historical writings, it has been concluded that the area of the project site might contain a significant number of valuable findings from the aspect of the state heritage. This study was performed by applying several research methods, namely interviewing informants, scientific survey studies, and scuba diving, to ensure any findings' accuracy and validity based on previous studies' literature review and historical writings. Some historical results were discovered during the research, and this was brought into several discussions regarding how the developer should adhere to regulations set by the National Heritage Department (JWN) to ensure that any development of sea reclamation projects in the state should comply with the importance of heritage, environment, and preserving areas with Outstanding Universal Value (OUV) in the state of Malacca.